Kidney transplantation in Icelandic patients, 2000–2019: are outcomes affected by low volume? - Palsson, Thordur P.; Andresdottir, Margret B.; Jonsson, Eirikur; Jonsson, Johann; Hilmarsson, Rafn; Indridason, Olafur S.; Palsson, Runolfur (Frontiers in Transplantation, 2024)
In Iceland, a small number of kidney transplants from living donors (LD) are performed at Landspitali-The National University Hospital (LUH) in Reykjavik, while deceased donor (DD) transplants have until recently invariably been carried out abroad. In this study, we evaluated the outcome of kidney transplantation in Icelandic patients.This was a retrospective study that included all Icelandic residents who underwent kidney transplantation recipients from 1 January 2000 to 31 December 2019. Data were obtained from the Icelandic End-Stage Kidney Disease Registry, medical records at LUH and the Scandiatransplant database. The CKD-EPI equation was used to calculate eGFR from serum creatinine for recipients and donors >18 years of age, and the modified Schwarts equation for those aged ≤18 years. Survival was estimated using the Kaplan-Meier method and the logrank test employed for group comparisons.A total of 229 kidney transplants in 221 patients were performed during the 20-year period, of which 135 were from LD (58.9%). During a median (range) follow-up of 7.4 (0.1-20) years, 27 patients (12.2%) died, 20 (74%) of whom had a functioning graft. One-year patient survival was 99.1% (95% confidence interval [CI], 97.9-100), 5-year survival 95.7% (95% CI, 92.7-98.7) and 10-year survival 87.7% (95% CI, 82.4-93.4). Death-censored graft survival was 98.3% (95% CI, 96.6-100), 96.8% (95% CI, 94.4-99.2) and 89.2% (95% CI, 84.1-94.7) at 1, 5 and 10 years, respectively.